The Use of Insecticide-Treated Curtains for Control of Aedes aegypti and Dengue Virus Transmission in “Fraccionamiento” Style Houses in México - Maria A. Loroño-Pino; Ana Uitz-Mena; Claudia M. Carrillo-Solís; Rocío J. Zapata-Gil; Dora M. Camas-Tec; Lourdes G. Talavera-Aguilar; Rosa C. Cetina-Trejo; Luis F. Flores-Flores; María C. Puc-Tinal; Clara Caamal-Jiménez; Guadalupe Reyes-Solís; Julián E. García-Rejón; et al. (Journal of Tropical Medicine)
Dengue, chikungunya, yellow fever, and Zika viruses transmitted by Aedes aegypti mosquitoes are major public health threats in the tropical and subtropical world. In México, construction of large tracts of “fraccionamientos” high density housing to accommodate population growth and urbanization has provided fertile ground for Ae. aegypti-transmitted viruses. We investigated the utility of pyrethroid-treated window curtains to reduce both the abundance of Ae. aegypti and to prevent dengue virus (DENV) transmission in fraccionamiento housing. Windows and doors of fraccionamiento homes in urban/suburban areas, where Ae. aegypti pyrethroid resistance associated with the Ile1016 knock down resistance (kdr) mutation in the voltage gated sodium channel gene was high, and in rural areas, where kdr resistance was low, were fitted with either insecticide-treated curtains (ITCs) or non-treated curtains (NTCs). The homes were monitored for mosquito abundance and DENV infection. ITCs reduced the indoor abundance of Ae. aegypti and the number of DENV-infected mosquitoes in homes in rural but not in urban/suburban study sites. The presence of non-treated screens also was associated with reduced numbers of mosquitoes in homes. “Super-infested” homes, yielding more than 50 mosquitoes, including DENV-infected mosquitoes, provide a significant public health risk to occupants, visitors, and people in neighboring homes.